Respuesta :
θ(t - 5) = 1 if t ≥ 5 and 0 otherwise, so the Laplace transform of the second derivative term is
[tex]\displaystyle \int_0^\infty q''(t) \theta(t-5) e^{-st} \, dt = \int_5^\infty q''(t) e^{-st} \, dt \\\\\\ = \int_0^\infty q''(t) e^{-st} \, dt - \int_0^5 q''(t) e^{-st} \, dt \\\\\\ = L_s\left\{q''(t)\right\} - \int_0^5 q''(t) e^{-st} \, dt[/tex]
Compute the remaining integral by parts.
[tex]u = e^{-st} \implies du = -se^{-st} \, dt \\ dv = q''(t) \, dt \implies v = q'(t)[/tex]
[tex]\implies \displaystyle \int_0^5 q''(t) e^{-st} \, dt = q'(t) e^{-st} \bigg|_0^5 + s \int_0^5 q'(t) e^{-st} \, dt = \dfrac{q'(5)}{e^{5s}} - q'(0) + s \int_0^5 q'(t) e^{-st} \, dt[/tex]
Integrating by parts again with similar choice of u and dv gives
[tex]\displaystyle \int_0^5 q'(t) e^{-st} \, dt = \dfrac{q(5)}{e^{5s}} - q(0) + s \int_0^5 q(t) e^{-st} \, dt[/tex]
Recall that
[tex]\displaystyle \int_0^\infty q''(t) e^{-st} \, dt = s^2 Q(s) - sq(0) - q'(0)[/tex]
[tex]\displaystyle \int_0^\infty q'(t) e^{-st} \, dt = s Q(s) - q(0)[/tex]
where Q(s) is the Laplace transform of q(t).
It follows that
[tex]L_s\left\{q''(t) \theta(t-5)\right\} = (s^2 Q(s) - s q(0) - q'(0)) - \left[\dfrac{q'(5)}{e^{5s}} - q'(0) + s \left(\dfrac{q(5)}{e^{5s}} - q(0) + s \int_0^5 q(t) e^{-st} \, dt\right) \right][/tex]
or
[tex]L_s\left\{q''(t) \theta(t-5)\right\} = s^2 Q(s) - \dfrac{sq(5)+q'(5)}{e^{5s}} - s^2 \int_0^5 q(t) e^{-st} \, dt[/tex]
Similarly, you can show that
[tex]L_s\left\{q'(t) \theta(t-5)\right\} = sQ(s) - \dfrac{q(5)}{e^{5s}} - s\int_0^5 q(t) e^{-st} \, dt[/tex]
and
[tex]L_s\left\{q(t) \theta(t-5)\right\} = Q(s) - \int_0^5 q(t) e^{-st} \, dt[/tex]
There's not much more one can say without knowing anything more about q(t) …